Planned EU laws on child sexual abuse have sparked a privacy row. Why? - Jones, Mared Gywn (euronews, 2023)
Some have argued the proposed EU law could usher in mass surveillance in the bloc through the scanning of all communications, including encrypted messages.
Europe
Keywords: 2023-10 October